STRATEGI KOMUNITAS BETAWI DALAM MEMPROMOSIKAN TRADISI PALANG PINTU (Studi Kasus Pada Event Festival Palang Pintu XI) - Ita Suryani; Asriyani Sagiyanto (Universitas Bina Sarana Informatika, 2017)
Palang Pintu traditions is one of the traditions that became the identity of Betawi people.Tradition became part of the procession of traditional wedding ceremony of Betawi since the time of the ancestors. The mix of silat and witty art of pantun became the dominant thing in the traditions of the Palang Pintu. This tradition can not be separated from the activities of Betawi people in it one Betawi cultural community that is Betawi Communication Forum or known FORKABI. Betawi community activities usually support in activities or Betawi Event, such as marriage Betawi, inauguration of the building, birthday Jakarta, festival Palang Pintu ect. Palang Pintu peformer are usually part of the Betawi community itself. So, in part, this part of Betawi community has an activity in introducing and promoting the tradisi palang pintu to the community, both in simple events and large national events. This research method qualitative descriptive method with approach of study of communication ethnography, where researcher want to see pattern of communication of a group that is Betawi community of FORKABI in promoting Tradition of Palang Pintu at Festival event of Palang Pintu XI. The conclusion shows that in promoting the traditions of the doorstop it is necessary for a movement and activity of one of the groups or communities that can introduce the traditions of the palang pintu to the community. The community is not just for promoting but it can also be a change agent that can help maintain and preserve the traditions of the palang pintu.Keywords: Strategic, Community, Promotion, Palang Pintu